The Impact of Online Learning on Early Childhood Social Behavior in Tk Pertiwi 2 Sidodadi Pekalongan Lampung Timur - Uswatun Hasanah; Aguswan Khotibul Umam; Khusnul Muslimah; Aufilana Rahmatika; Amirah Aliyah Marga (Journal of Childhood Development, 2021)
Online learning is learning that is carried out online, learning using applications or with social networks. This online learning is carried out without face to face directly, but through the media that has been provided. This study used a qualitative field method with descriptive research type. The main data sources in qualitative research are words and actions, the additional data is documentation. The results of this study are online learning carried out during the Covid-19 pandemic carried out at Kindergarten Pertiwi 2 Sidodadi Pekalongan, East Lampung in social emotional development, which is very impactful because there is no direct interaction between friends and teachers, but in the online learning process when the teacher has creativity in giving tasks to children such as involving parents and the environment in learning will develop social emotional in children. Some parents say that with online learning, children are not focus on learning and have fun playing alone.